Terrain Attributes and Drainage Texture as Indicators of Landslide Occurrence in a Part of Garhwal Himalaya, India - Awasthi, A. K.; Tabatabaei, S. H.; Singh, Bhawani; Mehrotra, G. S. (Journal of Nepal Geological Society, 1995)
Slope movement processes along with other terrain attributes influence surface morphology of an area. Correlation analysis of nineteen morphometric parameters and the landslide areal extent in 26 third order basins in a part of Garhwal region of the Lesser Himalaya, U.P. India, indicates that fraction of landslide area (Ls) in a basin has statistically significant correlation coefficient of about 0.86, 0.84, 0.68 and -0.55 (at 99% confidence level) with drainage texture (DT), stream frequency (SF), drainage density (DD) and basin circularity (BC) respectively. Drainage texture which is the product of stream frequency and drainage density, is one single morphometric parameter in a basin that has in it, the influence of many morphometric parameters which in turn, are reflection of the cumulative effect of elevation, slope, lithology, structural features, vegetation and hydrological condition. Higher the drainage texture, higher is the landslide areal extent. Based on regression analysis, a relationship between fraction of landslide area (Ls) and drainage texture (DT) of third order basin has been worked out which suggests that the third order basins always have some unstable slope faces. With a drainage texture of about 185, almost all the slopes are expected to be unstable. Relatively stable areas are associated with lower values of drainage texture. Circular basins with low relief have lower values of DT and therefore, their slopes are relatively more stable. This identified relationship is found to be useful within the error limit of 25 percent and is, therefore, recommended for use as a first step towards the landslide hazard zonation in similar terrains.